Minding the gender gap in digital innovations in Bangladesh’s agri-economy - Joshi, Deepa; Sarker, Farhana; Andarcia, Mariangel Garcia (International Water Management Institute, 2023)
Without a concerted effort to empower marginalized groups and bridge the digital gender gap, digitalization risks exacerbating disparities, leaving many behind in the digital revolution.